Role of Amyloid-β Glycine 33 in Oligomerization, Toxicity, and Neuronal Plasticity - Harmeier, Anja (J Neurosci, 2009)
The aggregation of the amyloid-β (Aβ) peptide plays a pivotal role in the pathogenesis of Alzheimer's disease, as soluble oligomers are intimately linked to neuronal toxicity and inhibition of hippocampal long-term potentiation (LTP). In the C-terminal region of Aβ there are three consecutive GxxxG dimerization motifs, which we could previously demonstrate to play a critical role in the generation of Aβ. Here, we show that glycine 33 (G33) of the central GxxxG interaction motif within the hydrophobic Aβ sequence is important for the aggregation dynamics of the peptide. Aβ peptides with alanine or isoleucine substitutions of G33 displayed an increased propensity to form higher oligomers, which we could attribute to conformational changes. Importantly, the oligomers of G33 variants were much less toxic than Aβ(42) wild type (WT), in vitro and in vivo. Also, whereas Aβ(42) WT is known to inhibit LTP, Aβ(42) G33 variants had lost the potential to inhibit LTP. Our findings reveal that conformational changes induced by G33 substitutions unlink toxicity and oligomerization of Aβ on the molecular level and suggest that G33 is the key amino acid in the toxic activity of Aβ. Thus, a specific toxic conformation of Aβ exists, which represents a promising target for therapeutic interventions.